Peranan Home Industry Rangginan Desa Kambeng Ponorogo Terhadap Perekonomian Keluarga - Risca Nur Firda; Nurma Fitrianna (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Home industry is one of the supporters of community empowerment in rural areas, especially women, Mrs. Muji's home industry rangginan is one of them. The problem in this study is one of the problems in people's lives, especially related to improving the welfare of the community, so in this study it is discussed about the home industry that can improve the economy of the family community to achieve community welfare. The purpose of this study was to determine the role of the Rangginan home industry in increasing the income of the families of the surrounding community and to explain the impact of the Rangginan home industry on increasing the family income of the surrounding community. The research used is field research using a qualitative approach. from the results of the study indicate that the home industry in an effort to improve the economy of the family of Mrs. Muji and the community is able to bring positive changes to the economy of the surrounding community. From an Islamic perspective, the role of Ibu Muji's home industry in the economy of Muji's family and the surrounding community in general has all fulfilled the basic objectives and concepts of Islamic economics and in accordance with related theories, but in recruiting the rich they tend to recruit non-permanent employees in order to empower the surrounding communit.